Práticas parentais na primeira infância em comunidades quilombolas na perspectiva dos papéis de gênero: uma revisão integrativa - Costa, Renan Vinícius de Freitas Guerra da (Brasil, 2024)
The objective of this research was to identify studies in the literature on parenting practices aimed at early childhood, from 0 to 5 years, within the context of quilombola communities and gender roles. This research is part of a national umbrella project on parenting and childhoods funded by the CNPq. Parenting is a multidimensional construct consisting of purposeful activities carried out by parental figures to ensure the survival, growth, and healthy development of children. To achieve this, an integrative review methodology was employed, using descriptors in Portuguese, Spanish, and English in the Web of Science, LA Referencia, and BVS databases. The final analysis focused on six articles, which indicated a predominance of health-related studies conducted by female researchers, specifically addressing quilombola motherhood. These studies aimed to observe the dynamics of child health practices, either aligned with or diverging from traditional quilombola practices. The results of the research were analyzed using content analysis methodology and theoretical models focusing on gender, intersectionality, and human development. Three analysis categories were formulated: Parenting practices; 2. Division of tasks and gender roles; and 3. Extended family: ancestries and relationship between systems. It was found that the results align with the adopted theoretical perspectives, opening avenues for future research and raising questions about how to address the specificities of traditional quilombola communities.